2022
DOI: 10.32843/bses.75-13
|View full text |Cite
|
Sign up to set email alerts
|

International Labor Migration During the Russian War Against Ukraine

Abstract: The article is devoted to the development of international labor migration during the Russian war against Ukraine. The purpose of the study is to determine the essence and features of international labor migration on the basis of the analysis of Ukrainian and foreign literary sources, and its tasks are to identify internal and external factors in the formation of Ukraine's migration potential; conducting of the classification of international labor migration; characteristics of changes that occur in internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The problem of international migration caused by Russia's war against Ukraine has especially exacerbated its destabilizing impact on cooperation between countries in the financial and economic sphere. Studying the negative trends in the influence of military factors on migration processes, Pavlov ( 2022) found that the phenomenon of international migration has acquired not only a global scale but also moved into the plane of political influence. Growing migration flows significantly overload recipient countries and causes destructive changes in the labor market of Ukraine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem of international migration caused by Russia's war against Ukraine has especially exacerbated its destabilizing impact on cooperation between countries in the financial and economic sphere. Studying the negative trends in the influence of military factors on migration processes, Pavlov ( 2022) found that the phenomenon of international migration has acquired not only a global scale but also moved into the plane of political influence. Growing migration flows significantly overload recipient countries and causes destructive changes in the labor market of Ukraine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The negative impact of military factors on international migration was proved by O. Pavlov [15], who revealed its cyclical nature and conditionality due to political instability in the country, and found that the processes of money transfer are insufficiently regulated, which causes an increase in the shadow economy level in the countries around the world.…”
Section: Literature Reviewmentioning
confidence: 99%